2012
DOI: 10.1002/cctc.201200705
|View full text |Cite
|
Sign up to set email alerts
|

Switching the Lactide Polymerization Activity of a Cerium Complex by Redox Reactions

Abstract: The old switcheroo! The ring‐opening polymerization activity towards meso‐lactide significantly differs when cerium complexes with two bis(phenolate) ligands (OSSO type) change their oxidation state from +4 to +3. This switch can be performed in situ by chemical reduction or oxidation of the catalyst. The redox switching is possible up to three times in a row. PLA=polylactide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 41 publications
(20 reference statements)
1
47
0
Order By: Relevance
“…The apparent polymerization rate constant (k app ) and polymerization rate constant (k p ) values were collected in Table 3. Similar activity trends were found 10 in the rac-LA polymerization as in L-LA polymerization that 1a had the highest activity (Table 3, entry [8][9][10][11][12][13][14][15][16][17][18][19]. A linear relationship between M n and rac-LA monomer conversion was observed ( Figure 6).…”
Section: Effect Of the Amino Alcohol Backbone Substituentsupporting
confidence: 75%
See 1 more Smart Citation
“…The apparent polymerization rate constant (k app ) and polymerization rate constant (k p ) values were collected in Table 3. Similar activity trends were found 10 in the rac-LA polymerization as in L-LA polymerization that 1a had the highest activity (Table 3, entry [8][9][10][11][12][13][14][15][16][17][18][19]. A linear relationship between M n and rac-LA monomer conversion was observed ( Figure 6).…”
Section: Effect Of the Amino Alcohol Backbone Substituentsupporting
confidence: 75%
“…Upon lactide polymerization, the chiral centers in the lactide monomer plays very important role in determining the mechanical, physical and degradation 10 properties of PLA. [4][5][6][7][8] Symmetric Salen Schiff base aluminum catalysts have achieved tremendous progress in the preparation of PLA polymers. [9][10][11][12][13][14][15] As far as we know, researches on half-Salen Schiff base complex were still not fully exploited.…”
Section: Introductionmentioning
confidence: 99%
“…Other chemically redox‐switchable catalysts have been designed that do not contain the ubiquitous ferrocene platform. In 2013, Mashima, Okuda, and co‐workers reported a system based on an anionic Ce III complex and a neutral Ce IV complex with two [OSSO]‐type dithiabis(phenolate) ligands ( XI ; Scheme ) 27. A cyclic voltammetry study showed that reduction of Ce IV to Ce III occurs at −1.51 V (vs. ferrocene) and that oxidation of the reduced species occurs at −1.01 V; this is followed by a second oxidation at +0.67 V, which was attributed to ligand oxidation.…”
Section: Switchable Catalysismentioning
confidence: 99%
“…Other examples of redox‐switchable catalysts, in which the oxidation state of the central catalytic metal changes during an oxidation–reduction cycle, have been reported by the groups of Okuda, Byers, and Lang. Okuda and co‐workers reported a redox‐switchable cerium complex with a dithiabis(phenolate) ligand . They demonstrated that by using the reduced form of the complex, ROP of meso ‐lactide proceeds 60 times faster than the polymerization with the oxidized form.…”
Section: Redox‐switchable Catalystsmentioning
confidence: 99%